“Do different personalities, different seats lead to different interactions?”: Personality Traits, Students’ Seating Location Preference and Student Engagement among Undergraduate Students - Lisa Desi Arimbi; Rose Mini Agoes Salim (Journal of Educational, Health and Community Psychology, 2026)
Students possess distinct personality traits, and during lectures, students also develop preferences regarding where they choose to sit in the classroom. The aim of this study is to examine the relationship between personality traits, students’ seating location preferences, and student engagement among university students. This study involved 574 undergraduate students in Indonesia employed a semi mix method approach. Multiple linear regression analysis conducted using RStudio version 4.5.1 (2025-06-13 ucrt). The regression model demonstrated that personality and seating location simultaneously statistically significantly contribute to all dimensions of student engagement (p<.01). Specifically, the model explained 41.45% of the variance of behavioral engagement, 38.33% of the variance of cognitive engagement, and 38.49% of the variance of emotional engagement. Partial regression analyses revealed that almost all personality dimensions significantly predict student engagement. Conscientiousness trait, extraversion trait, and intellect trait consistently predict all dimensions of student engagement (p<.05). However, agreeableness trait shows no statistically significant predicted cognitive engagement (p>.05) and emotional stability trait shows no statistically significant predicted behavioral engagement (p>.05).  Interestingly, the results demonstrate that only front-row seating preference negatively and statistically significantly impacts cognitive engagement (p<.05), while middle-row seating preference has no significant effect on any engagement dimensions (p>.05). These results suggest that instructors should encourage learning activities to foster students to persist, have curiosity, and explore knowledge. It’s essential for instructors to consistently provide an inclusive learning environment and opportunities for all students across seating locations whether seated in the front, middle, or back rows.